Differences in the limb blood flow between two types of blood flow restriction cuffs: A pilot study - Citherlet, Tom; Willis, Sarah J.; Chaperon, Audrey; Millet, Grégoire P. (Frontiers in Physiology, 2022)
Introduction: The determination of the optimal occlusion level is a key parameter in blood flow restriction (BFR). This study aimed to compare the effects of elastic (BStrong) vs. nylon (Hokanson) BFR cuffs on blood flow in the lower and upper limbs. Methods: Eleven healthy participants undertook several BFR sessions with 2 different cuffs of similar width on their lower and upper limbs at different pressures (200, 250, 300, 350, and 400 mmHg for BStrong and 0, 40, and 60% of the arterial occlusion pressure (AOP) for Hokanson). Doppler ultrasound recorded blood flows through the brachial and femoral artery at rest. Results: With BStrong, only 350 and 400 mmHg pressures were significantly different from resting values (0% AOP). With Hokanson, both 40% and 60% of the AOP were significantly different from resting values (p < 0.05). Discussion: While both cuffs elicited BFR, they failed to accurately modulate blood flow. Hokanson is appropriate for research settings while BStrong appears to be a convenient tool for practitioners due to its safety (i.e., the impossibility of completely occluding arteries) and the possibility of exercising freely detached from the pump.